Classification of audiovisual in the Netflix catalog: transmedias, fandoms and nichos - Araujo, Andrei Roberto; Antonio Sabbag, Deise Maria; Silva, Bruna Daniele Oliveira da [UNESP]; Belam, Denise Cristina [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2022)
In a scenario of global conjuncture, resources generated by the interne have become relevant regarding relationships and cyber communication. The rising of virtual movements, which initiated a new social-historical perspective of communities and their own vocabularies in the digital environment, have reduced barriers and brought people and social networks closer, according to their ideas and similarities. To carry out this work, we brought as a sample a streaming platform, a means of use and distribution of digital content, without the need for data storage by the user. Considering Netflix as a platform strongly present into society, we proposed a comparative analysis on the classification and organization of information in the catalogs that are part of Netflix. For this purpose, we selected four samples present in the catalog, and defined that in order to meet the criteria for the study, they needed to integrate the culture of convergence (transmedia, fandoms and niche market): Productions in series format and Netflix Original Productions. It is believed that the objectives were achieved, but some points are worth mentioning: beside the lack of historical scientific bibliography on the subject, chain divisions were noted only on the terms visible on screen; the division did not follow a hierarchy, making the classification system flawed and poorly structured, without showing important aspects of extension and comprehension.
Keywords: Classification; Knowledge organization; Classification Theory; Netflix